2020
DOI: 10.3329/bjms.v19i2.45014
|View full text |Cite
|
Sign up to set email alerts
|

Dravet Syndrome -A case report from Aseer, Saudi Arabia

Abstract: Dravet syndrome (DS) is an epileptic encephalopathy that presents with protracted seizures in infancy, associated with fever, and frequently categorized as febrile seizure at first presentation. In the second year, myoclonia, atypical absence and complex partial seizures develop. The correct diagnosis of DS and appropriate follow-up are delayed until after appearance of signs of developmental regression in the second year of life. Timely detection and diagnosis of DS followed by management with suitable antico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…In Lebanon, a study carried out on 8 patients showed similarity with our patient with regards to seizure presentation, age at first presentation, and the absence of a family history of seizures [ 5 ]. Another case report on Dravet syndrome conducted in Saudi Arabia revealed no remarkable radiological findings [ 6 ]. However, our patient had mild cerebellar vermis atrophy in the MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In Lebanon, a study carried out on 8 patients showed similarity with our patient with regards to seizure presentation, age at first presentation, and the absence of a family history of seizures [ 5 ]. Another case report on Dravet syndrome conducted in Saudi Arabia revealed no remarkable radiological findings [ 6 ]. However, our patient had mild cerebellar vermis atrophy in the MRI.…”
Section: Discussionmentioning
confidence: 99%